Are admission laboratory values in isolation valuable in predicting surgical outcome in patients with perforated peptic ulcers: a retrospective, cohort analytical, observational study - Mulder, Wikus Wessel (University of the Free State, 2021)
Background: Perforated peptic ulcer carries a noteworthy mortality, and admission status is a significant prognosticator thereof. Laboratory values are objective and readily available and therefore ideal for risk stratification. The objective of the study is to calculate the predictive value of admission laboratory values in patients with perforated peptic ulcers. Methods: A retrospective, cohort analytical, observational study was performed. All patients with surgically confirmed perforated peptic ulcers at Pelonomi Tertiary Hospital from July 2014 to June 2019 were considered. Demographic data and admission laboratory values were collected from hospital and laboratory electronic databases and theatre books. Outcomes measured were in-hospital mortality, ICU admission and length of stay in ICU and in hospital. The significance of categorical variables was calculated by Chi-square and Fisher’s exact test. Logistic regression analysis considered univariately statistically significant variables. A p-value of < 0.05 was considered statistically significant. Results: Over the 5 years 188 patients met the inclusion criteria. The median age was 46 years (15-87) with a male predominance of 71.3 % (N=134). The median length of hospital stay was 7 days (1-94) and 31.4% (N=59) of patients were admitted to the Intensive Care Unit. Operative in-hospital mortality was 25.0% (N=47). Predicting the two categorical outcomes of in-hospital mortality and ICU admission abnormal haemoglobin, platelet count, urea, creatinine and potassium were all found to be statistically significant in univariate analysis. For in-hospital mortality age (OR 1.03 [95% CI 1.01-1.06]), haemoglobin (OR 4.36 [95% CI 0.98-19.39]),) and creatinine (OR 7.76 [95% CI 2.90- 20.74]),) were significant in multivariate analysis and for ICU admission age (OR 1.03 [95% CI 1.00-1.05]),), platelet count (OR2.94 [95% CI 1.24-7.01]),) and creatinine (OR 6.90 [95% CI 2.87-16.61]),). Urea ≥ 10.9mmol/L showed a sensitivity of 70.2% and specificity of 82.1% (AUC 0.79) and creatinine ≥ 109umol/L a sensitivity of 80.9% and specificity of 67.7% (AUC 0.80) in predicting in-hospital mortality. Conclusions: The mortality rate in patients with perforated peptic ulcer disease is still substantial. Admission laboratory values shows statistical significance as outcome indicators and are valuable to assist in predicting prognostication. Abnormal high serum creatinine was the strongest single predictor of both mortality and ICU admission.
Keywords: Peptic ulcer perforation; Mortality; Laboratory values; Prognostic factors; Emergency surgery; Peptic ulcer -- Pathogenesis